COMPLEMENTARY AND ALTERNATE HEALTHCARE: “AROMATHERAPY” - Sidaveerappa Balappa Tuppad (Indian Journal of Psychiatric Nursing)
The purpose of this review is to describe the concepts of alternative therapies and aromatherapy pertaining to nursing literature. Furthermore, empirical findings of aromatherapy in research will be presented, and applied theories were narrated. An integrative literature search was executed. The total number of relevant citations 30 was found. The search results were reviewed, and key points were extracted in a standardized form. Extracts were then qualitatively summarized according to relevant aspects and categories for the review. Aromatherapy - is a form of alternative medicine that uses volatile plant materials, known as essential oils, and other aromatic compounds for the purpose of altering a person's mind, mood, cognitive function or health.” The main purpose of aromatherapy in the mental health setting is to influence the patient's health status and state of well-being. The included citations all conclude that aromatherapy can be used to a certain degree. Nursing science has to integrate aromatherapy into nursing care